Antioxidant Effects of Turmeric Leaf Extract against Hydrogen Peroxide-Induced Oxidative Stress In Vitro in Vero Cells and In Vivo in Zebrafish - Sera Kim; Mingyeong Kim; Min-Cheol Kang; Hyun Hee L. Lee; Chi Heung Cho; Inwook Choi; Yongkon Park; Sang-Hoon Lee (Antioxidants, 2021)
Oxidative stress, caused by the excessive production of reactive oxygen species (ROS), results in cellular damage. Therefore, functional materials with antioxidant properties are necessary to maintain redox balance. Turmeric leaves (Curcuma longa L. leaves; TL) are known to have antioxidant properties, including 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2′-Azino-di-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS), and Hydrogen peroxide (H2O2) radical scavenging activity in several studies. The antioxidant effects of TL come from distinct bioactive compounds, such as curcumin, total phenolic compounds, and flavonoids. Therefore, in this study, the antioxidant effects of a water extract of TL (TLE) against H2O2 treatment were assessed in vitro Vero cells and in vivo zebrafish models. The intracellular ROS generation and the proportion of sub-G1 phase cells were evaluated in H2O2- or/and TLE-treated Vero cells to measure the antioxidant activity of TLE. TLE showed outstanding intracellular ROS scavenging activity and significantly decreased the proportion of cells in the sub-G1 phase in a dose-dependent manner. Furthermore, cell death, ROS generation, and lipid peroxidation in the H2O2-treated zebrafish model were attenuated as a consequence of TLE treatment. Collectively, the results from this study suggested that TLE may be an alternative material to relieve ROS generation through its antioxidant properties or a suitable material for the application in a functional food industry.